Real-life efficacy of guselkumab in patients with early psoriatic arthritis. (21st June 2021) - Pantano, Ilenia; Mauro, Daniele; Romano, Francesca; Gambardella, Alessio; Valenti, Mario; Simone, Davide; Iacono, Daniela; Costanzo, Antonio; Argenziano, Giuseppe; Ciccia, Francesco
Abstract: Objectives: To assess the efficacy of the novel anti-IL-23 monoclonal antibody guselkumab in a real-life observational cohort of patients with early PsA. Methods: We conducted an observational study on patients with early PsA followed by the joint dermatology-rheumatology clinics of two Italian centres starting therapy with guselkumab for severe skin involvement. Each patient was evaluated at baseline and every 24 weeks for one year, recording Disease Activity Index for PsA (DAPSA), PASI, VAS Pain, VAS Prutitus, Patient's Global Assessment (PtGA) and assessing DAPSA response. Results: Twenty-four patients were recruited (16 women). The mean duration of skin disease was 12.5 years (CI 8; 17), but all patients had a shorter articular disease duration, 21.29 months (CI 15.9; 26.68). At baseline, all patients displayed a moderate cutaneous disease with a mean PASI of 15.2 (CI 11.7–18.6) and high disease activity, characterized by mean DAPSA of 26.84 (CI 22.49–31.19). An inflammatory low back pain was reported by five patients (20%) with a mean BASDAI 5.1 (CI 4, 38–5, 85) at baseline. The majority of guselkumab-treated patients ( n = 18; 75%) reached DAPSA remission or DAPSA low disease activity after six months. Seventeen out of 24 patients completed 12 months of treatment, 11 of them (65%) in low disease activity, six (35%) in remission. All patients with axial disease reported improvement of inflammatory low back pain at week 24 with a mean BASDAI 2.98 (CI 2, 18– 3, 77). No significant side effects were reported. Conclusions: Real-life data on a cohort of early PsA patients confirm the efficacy and safety of guselkumab on peripheral and axial manifestations.